Introduction to the Core Concepts of Christian Psychotherapy - Ilievski, Prof. Naum; Angelina Ilievska (European Journal of Multidisciplinary Studies, 2019)
Christian psychotherapy comes out of the two-thousand year long spiritual practice in Christianity. Its core is based upon the foundations of Christian anthropology, which defines and focuses on the human soul. The purpose of this paper is to establish Christian psychotherapy as a contemporary theory of personality development, with its own method that enables personality development and growth to a complete spiritual self-actualization and self-realization. Christian psychotherapy opens a new perspective towards man’s psychological and spiritual functioning; a new dynamic model is offered for his inner functioning – not only at a psychological, but also at a spiritual level – which is useful and practically applicable with the other trends in psychotherapy. Via a descriptive method, the basic concepts are defined: (1) Stages of spiritual development; (2) A comparative parallel between the stages of spiritual development and the stages of spiritual and mental disorders with clinical psychopathological entities; (3) Primary and secondary function of the mind; (4) The FCP method (systematized by the author), which has a central role, and the client-therapist relationship; The systematization of the spiritual development of personality is found only within the frames of Christian psychotherapy; this type of systematization of the spiritual development – including a parallel comparison with the three stages of spiritual and mental disorders – has been introduced for the first time.